Effects of Bacillus subtilis and commercial probiotic in growth of red tilapia (Oreochromis sp.) - Yasmi Awang.
The objective of this experiment was to determine the effects of Bacillus subtilis and a commercial probiotic on growth of juvenile red tilapia (Oreochromis sp.). Red juvenile tilapia at an initial average size of 3 to 5cm per fish, with stocking density of 30 fish per aquarium was used. The study was conducted at the Hatchery Complex of the Department of Aquaculture, Faculty of Agriculture, UPM in Puchong, Selangor, from December 2007 till February 2008. The experiment was carried out with three different treatment which consisted of T1(control), T2 (Bacillus subtilis) and T3 (commercial probiotic). Each treatment was replicated three time and conducted in a recirculation system in glass aquaria for 9 weeks. The result obtained from this experiment showed that treated juvenile red tilapia (Oreochromis sp.) growth differs significantly (P<0.05) as compared to control.